Diseño e implementación de un sistema de control de focos incandescentes en los hogares por medio de un control remoto universal - Yagual, J. (2009)
This paper presents the design and implementation of an incandescent bulbs control system through an universal remote control unit making it suitable for household market and the needs of modern lighting technology. It describes the lighting background and how modern technological developments have given the way to solutions currently proposed for any domotic system, it explains the approach to these solutions, and introduces justification and scope of the present project. The paper details also the technical bases to be used to carry out the project implementation, this is, the study of the infrared communication protocols and the selection of the most appropriate, the use of the microcontroller and its benefits to the requirements of the system. Subsequently it describes the design phase including the power supply, zero crossing detector, power circuit, infrared sensor, keyboard and the microcontroller programming algorithms, as well as the explanation of the device operation control. Finally, it shows the result of the device tests demonstrating optimum performance.